PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TEAM GAME TOURNAMENT (TGT) TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PPKN KELAS VIII DI SMP NEGERI 5 MUARO JAMBI - Mustamiroh, Mustamiroh; Sutja, Akmal; Maulia, Siti Tiara (Fakultas Keguruan dan Ilmu Pendidikan, 2023)
This research aims to determine the effect of the team game tournament type cooperative learning model on student learning outcomes in class VIII Civics subjects at SMP Negeri 5 Muaro Jambi. This research was motivated by low student learning outcomes. This research method uses a quasi experimental design with a Nonequivalent Pre-test Post-test control Group Design. This research was conducted at SMP Negeri 5 Muaro Jambi in the 2023/2024 academic year. The population in this study was class VIII and the sample for this study used two classes as sample groups, namely having a total of 40 students. The sampling technique for this research was total sampling. The data collection technique uses tests in the form of Pre-test and Post-test in the experimental class and control class. The data was tested using SPSS software version 24 for Windows. The research results showed that there was an influence of the team game tournament type cooperative learning model on student learning outcomes in class VIII Civics subjects at SMP Negeri 5 Muaro Jambi. This study uses nonparametric statistical tests because the data is not normally distributed. Next, the Mann Whitney test was carried out on the Asymp Sig value. (2-tailed) 0.002 < 0.05. in accordance with Asymp Sig decision making. (2-tailed) < 0.05, it can be concluded that Ho is rejected and Ha is accepted. So that the application of the team game tournament (TGT) type cooperative learning model influences student learning outcomes in class VIII Civics subjects at SMP Negeri 5 Muaro Jambi.